Patient-Derived HIV-1 Nef Alleles Reveal Uncoupling of CD4 Downregulation and SERINC5 Antagonism Functions of the Viral Pathogenesis Factor. (1st October 2020) - Obermaier, Benedikt; Ananth, Swetha; Tibroni, Nadine; Pierini, Virginia; Shytaj, Iart L.; Diaz, Ricardo S.; Lusic, Marina; Fackler, Oliver T.
Abstract : Supplemental Digital Content is Available in the Text.